Implementation of Preoperative Screening Protocols in Otolaryngology During the COVID-19 Pandemic. (August 2020) - Urban, Matthew J.; Patel, Tirth R.; Raad, Richard; LoSavio, Phillip; Stenson, Kerstin; Al-Khudari, Samer; Nielsen, Thomas; Husain, Inna; Smith, Ryan; Revenaugh, Peter C.; Wiet, R. Mark; Papagiannopoulos, Peter; et al.
Objective: To highlight emerging preoperative screening protocols and document workflow challenges and successes during the early weeks of the COVID-19 pandemic. Methods: This retrospective cohort study was conducted at a large urban tertiary care medical center. Thirty-two patients undergoing operative procedures during the COVID-19 pandemic were placed into 2 preoperative screening protocols. Early in the pandemic a "high-risk case protocol" was utilized to maximize available resources. As information and technology evolved, a "universal point-of-care protocol" was implemented. Results: Of 32 patients, 25 were screened prior to surgery. Three (12%) tested positive for COVID-19. In all 3 cases, the procedure was delayed, and patients were admitted for treatment or discharged under home quarantine. During this period, 86% of operative procedures were indicated for treatment of oncologic disease. There was no significant delay in arrival to the operating room for patients undergoing point-of-care screening immediately prior to their procedure ( P = .92). Discussion: Currently, few studies address preoperative screening for COVID-19. A substantial proportion of individuals in this cohort tested positive, and both protocols identified positive cases. The major strengths of the point-of-care protocol are ease of administration, avoiding subsequent exposures after testing, and relieving strain on "COVID-19 clinics" or other community testing facilities. Implications for Practice: Preoperative screening is a critical aspect of safe surgical practice in the midst of the widespread pandemic. Rapid implementation of universal point-of-care screening is possible without major workflow adjustments or operative delays.